Hygroscopic property of inorganic salts in atmospheric aerosols measured with physisorption analyzer. (15th February 2021) - Zhang, Qing-Nuan; Zhao, Li-Jun; Chen, See-Hua; Guo, Xin; Luan, Ye-Mei; Zhang, Yun-Hong
Abstract: Hygroscopicity is capable of significantly affecting atmospheric visibility, radiative forcing, and cloud condensation nuclei process. Herein, a physisorption analyzer was adopted to determine the hygroscopicity of inorganic salt particles in atmospheric aerosols (e.g., NaNO3, NaClO4, MgSO4, K3 PO4, K2 HPO4, and KH2 PO4 ) at 298 K. By regulating the ambient relative humidity (RH), qualitative and quantitative information of the mentioned particles in humidifying and dehumidifying cycles was acquired. The deliquescence relative humidity (DRH) and efflorescence relative humidity (ERH) were measured, and supersaturation was observed and recorded during the dehumidification process. The water-to-salt molar ratios (WSR) of the mentioned inorganic salts depending on RH were determined, and the hygroscopic results of NaNO3 and NaClO4 particles were well consistent with the results achieved with other methods or by theoretical prediction. This study fitted WSR-to-RH equations suitable for NaNO3, NaClO4, MgSO4, K3 PO4, and K2 HPO4 particles. The adsorption heats for monolayer water molecules in the mentioned inorganic salt particles are calculated. The present study lays a solid foundation for gaining insights into the effects of RH on atmospheric aerosols. Highlights: Physisorption analyzer is used to study the hygroscopicity of NaNO3, NaClO4, MgSO4, as well as K3 PO4, K2 HPO4, KH2 PO4 particles. The water-to-salt molar ratio curves of these inorganic salts were determined. Deliquescence relative humidity for NaNO3 (74.5% RH), NaClO4 ·H2 O (46.9% RH) can be measured. In the deliquescence process, MgSO4 appears a colloidal state, and K3 PO4 and K2 HPO4 appears a supersaturation state. Supersaturated and crystalline hydrates are observed.